COMPOSITION ANALYSIS OF CALCIUM AND SULFUR ON GYPSUM AT THE PUGER DISTRICT JEMBER REGENCY AS AN ALTERNATIVE GYPSUM DENTAL MATERIAL: ANALISIS KIMIA KANDUNGAN KALSIUM DAN SULFUR PADA GIPSUM DI KAWASAN PUGER KABUPATEN JEMBER SEBAGAI ALTERNATIF GIPSUM DI BIDANG KEDOKTERAN GIGI - Amiyatun Naini; Dessy Rachmawati (TALENTA, 2010)
Gypsum is a material used in medical dentistry, as dental casting material, dental model, base for dental model andinvestment material. The gypsum used in medical dentistry is Hydrated Calcium Sulfate (CaSO 4 2H 2 O). Puger districtat Jember regency is well known as a mining area that produces abundant amount of gypsum. This research was aimed toanalyz e the calcium and sulfur composition of the gypsum from Puger district as an alternative material in dental practice.The total samples were 48, and divided into four groups, The first group contained of gypsum mined from low level land.Th e second group was the gypsum mined from middle level land, and the third group was the gypsum mined from upperlevel land. While the fourth group was the gypsum commonly used in dentistry. Calcium composition was analyzed usingAtomic Absorption Spectroph otometer (AAS) with wavelength of 285 nm, w hile sulfur composition analyzed usingspectrophotometer 21 D with 432 nm wavelength. T he result showed that compositions of calcium and sulfur of thegypsum groups w as significantly different (p < 0.05). In c onc lusion , Gypsum at Puger district has adequate calcium (Ca)and sulfur (S) composition to be used as an alternative gypsum in medical dentistry.